OPTIMAL IDENTIFICATION OF RANDOM EVENTS - Boris N. Chugaev; Alexander Y. Arzhenenko (Статистика и экономика)
The paper presents a method for optimizing identification of random events by using the theory of questionnaires. Theory questionnaires - a branch of mathematics that arose at the turn of mathematical statistics, combinatorics, graph theory and information theory. Its founder K.F.Pikar developed this theory as a description of the device logical relationships of tasks and methods of their solutions and the conditions under which these decisions are made. PP Parkhomenko suggested using questionnaires theory as a mathematical device to illustrate the construction, presentation and description of the best conventional diagnostic algorithms.The main task of the theory of the questionnaires was to build optimal in some sense of the questionnaire.